Is the desire to help people the main motivation for entering a medical profession? A cross-cultural, phenomenological study - Cornelis A. J. De Jong; Lisa Wang; Leendert C. van Rijn; Shelly Iskandar; Darius Jokūbonis; Maarten J. van der Laan (Academia Mental Health & Well-Being)
Discrepancies between motivation and the realities of becoming a physician can lead to burnout and thus physician shortages. Personal motivation appears to be a predictor of success, but modern medical education does not sufficiently emphasize it. This study aims to better understand individual motivation for becoming a physician. Residents and interns in psychiatry were asked about their reasons for choosing to become physicians. Twelve individuals with different medical backgrounds categorized these reasons through a card-sorting task. Through co-occurrence analysis, categories were identified and named by consensus. Among the 86 participants, 270 reasons were cited. Nine categories were identified, listed in the order of frequency: helping people, interest in the human body, job/financial security, work context, initiated by family/parents, interesting/challenging/practical, respected profession, long-held dream, and problem-solving/finding answers. Interest in the human body was significantly greater among younger participants, while motivation to help people increased significantly with age. In Lithuania and Indonesia, helping people was the primary motivation for becoming a doctor, whereas in the Netherlands, interest in the human body was the most frequently mentioned reason. The Netherlands also mentioned interest in the human body and the interesting/challenging/practical category significantly more often. Examining motivation for becoming a physician provides insight into differences in motivational profiles. These profiles can be compared to physicians’ daily practice across medical disciplines. Such reflection can help identify potential incompatibility between initial motivation and the demands of specific medical disciplines. This may help reverse the trend of declining vitality of the medical profession.